A Multidimensional Model of Pre-Writing Competence in Special Education Students: Validation Using Confirmatory Factor Analysis (CFA) Approach - Sulasminah, Dwiyatmi; Meidina, Tatiana (International Journal of Environment, Engineering and Education, 2025)
Children with cerebral palsy (CP) face distinct challenges in pre-writing acquisition, yet existing assessment tools often prioritize motor deficits while overlooking environmental barriers. This study aimed to validate a multidimensional measurement model of pre-writing challenges and supports for students with CP in Indonesian special schools. Grounded in the ICF-CY, HAAT, and Universal Design for Learning (UDL) frameworks, the model comprised four latent constructs: motor impairment to writing (MIW), pre-writing activity difficulties (PAD), inclusive learning environment (ILE), and adaptive pre-writing media (APM). A total of 108 students with CP in the pre-writing stage were rated by their teachers using a 5-point Likert questionnaire. Confirmatory Factor Analysis (CFA) was conducted with IBM SPSS AMOS to examine model fit, factor loadings, and reliability. After removing poorly performing indicators, the final model with four factors and 19 indicators demonstrated excellent fit (Chi Square= 1.01, p = 0.43, CFI = 0.998, TLI = 0.997, RMSEA = 0.007, PNFI = 0.79). All standardized factor loadings ranged from 0.59 to 0.94 (p < 0.001), and Cronbach’s alpha values for the four constructs were between 0.87 and 0.89, indicating high internal consistency. Moderate to strong inter-factor correlations were found, particularly between PAD and ILE, highlighting the close interplay among functional limitations, activity demands, and classroom conditions. The validated instrument offers a concise framework for identifying pre-writing challenges and environmental supports in students with CP. It can inform individualized intervention planning, the design of inclusive learning environments, and the development of adaptive pre-writing media in resource-constrained settings.